The Redevelopment of Ya’ahowu Park with Creative Placemaking in Gunungsitoli City - Amanta Halawa, Oscar (International Journal of Architecture and Urbanism, 2023)
One of the elements of a city that is considered capable of supporting the quality of the environment and the quality of urban life is public open spaces. Ya’ahowu Park in the Municipality of Gunungsitoli is a public open space that serves social, cultural, and economic functions. As an area that is continually developing, issues arise due to the increasing intensity of its use as a coastal tourism destination and culinary center. The current arrangement of the site is still partial, purely aesthetic, and lacks a master plan as a guide. Therefore, if its development is not properly planned, it is feared that it may exacerbate problems and worsen the site’s quality. This thesis aims to design the development of Ya’ahowu Park as a public open space for tourism, using the waterfront concept and a placemaking approach. These theories are employed because they are relevant to the physical conditions of the design site, with the hope of creating a quality and meaningful public space for its users. The focus of the development is on the waterfront redevelopment, as an effort to reorganize the waterfront area along with the facilities that can still be utilized. The previous facilities are restored and/or reactivated during the planning process, but with new roles that lean more towards public interests, with the objective of improving the environmental quality. Creative placemaking is the central approach, aiming to enliven the place, stimulate the economy, and provide a platform for creativity with local wisdom.